IMPLEMENTING PROJECT-BASED LEARNING THROUGH HISTORICAL SONG VIDEO CLIPS: A QUALITATIVE STUDY OF STUDENTS’ COLLABORATIVE SKILLS - Resdiantari, Offy; Barontuko, Maulano; Rokhman, Muhamad Nur (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
This study describes the implementation of Project-Based Learning (PjBL) through a historical song video clip project and its contribution to strengthening students’ collaborative skills at SMA Negeri 7 Purworejo. The research employed a qualitative descriptive design involving 12th-grade science students. Data were collected through classroom observations conducted during the project implementation, semi-structured interviews with the history teacher and several actively involved students selected purposively, and documentation of students’ video products. The analysis was carried out using thematic coding based on a collaborative skills framework comprising five dimensions: negotiation, advocacy, cooperation, communication, and conflict management. The findings indicate that the project-based activities created opportunities for students to engage in shared decision-making, distribute responsibilities, articulate ideas, and manage differences constructively during the video production process. These results suggest that creative digital projects within a structured PjBL framework can meaningfully support the development of collaborative competencies. The study also highlights the role of teacher facilitation and institutional support in sustaining collaborative learning practices in secondary education settings.